Impact of physician−pharmacist collaborative protocol-based pharmacotherapy management for HIV outpatients: a retrospective cohort study - Kimihiko Urano; Miki Ishibashi; Takeshi Matsumoto; Kohshi Ohishi; Yuichi Muraki; Takuya Iwamoto; Junichi Kunimasa; Masahiro Okuda (BMC, 2020)
Abstract Background Effective treatment for human immunodeficiency virus (HIV) infection requires close cooperation among healthcare professionals. This is because maintaining continuity with treatment regimens is important in anti-HIV therapy. In addition, explaining medication use is more important than that for other diseases. Since 2010, pharmacists at the Mie University Hospital have been interviewing patients, selecting drugs, and formulating medication plans for HIV-positive patients. In August 2011, we established the physician and pharmacist-led collaborative Protocol-based Pharmacotherapy Management (PBPM) to increase the efficacy and safety of treatment, while reducing the burden on physicians. In the present study, we evaluated the outcomes associated with PBPM for HIV pharmacotherapy. Methods We prepared protocols for drug selection, timing of interventions, and methods of intervention according to various guidelines. This study included 40 HIV-positive patients receiving outpatient care between January 2009 and February 2017. Of these patients, 17 received treatment before implementing PBPM and 23 patients received treatment afterward. We compared the intervention parameters between before and after the implementation of PBPM. Results The proportion of patients receiving prescription proposals from pharmacists was markedly higher after introducing PBPM (6 out of 17 patients vs. 23 out of 23 patients). All prescription proposals were accepted by physicians before and after PBPM. The number of interviews before antiretroviral therapy (ART) initiation (median [range]) decreased from 2 [1-5] to 1 [1-3] after PBPM introduction, suggesting the time to introduction of treatment has been shortened. Before the introduction of PBPM, nine patients required a change in their ART prescriptions and four patients were hospitalized (one patient was hospitalized due to an error in the self-administration of anti-HIV medicines, two patients were hospitalized due to interruptions in medication, and one patient was hospitalized for the treatment of other diseases). Only one patient was hospitalized after PBPM, and was unrelated to drug adherence. The proportion of patients with a reduced HIV-RNA load increased from 71 to 100%. Furthermore, the proportion of patients who maintained levels below the limit of quantitation increased from 59 to 91% after implementing PBPM. Conclusion The implementation of PBPM for HIV outpatients improves the efficacy and safety of HIV pharmacotherapy.